Sequential Mycoplasma pneumoniae pneumonia and Chromobacterium violaceum skin abscess in a pediatric patient: Chromobacterium violaceum infection in a child - Guo, Weizhen; Li, Iris Wai Sum; Li, Xi; Xu, Hua; Lu, Dongrong; Liu, Yue; Chen, Jiukai; Mok, Chris Ka Pun; Zhou, Yingchun (The Journal of Infection in Developing Countries, 2017)
Mycoplasma pneumoniae is a common atypical respiratory pathogen causing community-acquired pneumonia in children. Co-infection with other respiratory viruses is common in pediatric patients but super-infection with bacteria other than Streptococcus pneumoniae and Haemophilus influenzae is rare. The first case of Chromobacterium violaceum infection incubated during and manifested after pneumonia caused by Mycoplasma pneumoniae in a 12-month old girl without any known history of immunodeficiency is here reported. The patient developed fever with redness and swelling over the middle phalanx of the right hand index finger which progressed to the formation of skin abscess. Following a course of intravenous meropenem and surgical drainage of the skin abscess, the patient fully recovered and was discharged.